An Illumination Representation Approach to the Chevreul Effect. (June 2015) - Schlüter, Nick; Golz, Jürgen
Within cognitive science of brightness and color perception, the argument has repeatedly been brought forward that it is necessary to consider mental representations for illuminations as well as mental representations for surfaces as integral elements of the functional architecture of the perceptual system. Here, we show that such an approach of dual semantic categories for perceptual representations can fruitfully be applied to the Chevreul effect, a brightness phenomenon of enhanced contrast at borders that played a prototypical role for a very different type of approaches. In these approaches, mechanisms processing retinal intensities are postulated that result in just one brightness dimension without explicitly referring to semantic categories of the perceptual system (surface vs. illumination representation). We argue that the Chevreul effect arises as a result of an interpretation by the visual system that the Chevreul stimulus is covered by a gradual illumination. Our first experiment shows that the Chevreul effect diminishes substantially when this interpretation is prevented by separating the elements of the Chevreul stimulus in depth. In the second experiment, we show that the strength of the Chevreul effect is strongly affected by embedding the Chevreul stimulus into three-dimensional scenes that either support or conflict with the interpretation of an illumination gradient across the stimulus.